Aqueous-organic biphasic redox-chemistry of high-hydride content rhodium clusters: Towards immobilisation of redox-switchable H-2 binding materials on a surface - Hiney, R; Marken, F; Raithby, P; Weller, A (2009)
Water-insoluble phosphine-surface-stabilised rhodium clusters [Rh6 (PR3)6 H12] [BAr4F]2 (R = cyclohexyl, ArF = (3,5-CF3)2C6H3) can be immobilised onto suitable glassy carbon, graphite, or tin-doped indium oxide (ITO) electrode surfaces. When immersed into alcohol/aqueous electrolyte media, they display stable voltammetric responses consistent with the formation of organic microdroplet | aqueous electrolyte two-phase conditions which are similar to those observed in corresponding anhydrous (CH2Cl2) solution phase. This results in an electrode surface that is straightforwardly modified with cluster materials that can uptake or release dihydrogen depending on their redox-state. The results presented herein lead to a slight re-evaluation of the originally reported hydrogen store and release cycle for this system. © 2009 Elsevier B.V. All rights reserved.